MODERASI BERAGAMA DAN LITERASI KEAGAMAAN: RESPON SISWA MADRASAH TERHADAP ISU RADIKALISME DAN INTOLERANSI - Dianto, Icol; Fikri, Sholeh; Siregar, Martua Haholongan; Efendi, Erwin; Dalimunthe, Tua (Yayasan Baitul Hikmah al-Zain, 2025)
This study aims to analyze the level of understanding of Madrasah Aliyah Negeri 3 Central Tapanuli students about religious moderation, religious literacy, and response to the issue of radicalism in the madrasah environment. The research approach uses a qualitative method strengthened with quantitative data through the distribution of a Likert scale questionnaire to 25 grade XII students. The data was analyzed descriptively by reviewing four main indicators: religious moderation, religious literacy, radicalism and attitudes towards differences, as well as social media and digital moderation. The results of the study showed that all aspects were in the